Pengaruh Pemberian Pakan Komplit Berbasis Silase Campuran Sorghum dan Daun Gamal ada Tingkat Beragam Terhadap Status Fisiologis Kambing Betina Lokal - Muheng, Yohana Heldiana; Abdullah, Muhammad S.; Sobang, Yohanis U. L. (Animal Agricultura, 2024)
This study considered these points and determined the impact on physiological status based on a mixture of sorghum and gamal silage produced at various levels on the physiological status (rectal temperature, heart rate and respiratory frequency) of local female goats. The livestock used in this research were 4 local female goats aged 6-8 months with a body weight range of 11-15 kg with an average of 12.88 kg. The method used is an experimental method with a Latin Square Design (RBSL) which consists of 4 treatments and 4 condensations P0 = Add up to silage feed mixed with 80% sorghum and loose gamal + 20% concentrate P1 = Add up to silage feed mixed with sorghum and 70% gamal + 30% concentrate P2 = Add up to silage feed mixed with sorghum and 70% gamal + 30% concentrate P2 = Add up to silage feed mixed with Sorghum and 60% gamal + 40% concentrate P3 = Add up to mixture Sorghum rolled silage and 50% gamal + 50% . The results obtained in this study were rectal temperature (oC) P0 37.58 ± 0.45, P1 37.1 ± 0.49, P2 37.45 ± 0.33 P3 37.13 ± 0.87, heart rate ( times/minute) P0 83.75±2.98, P1 81.75 ±2.21, P2 81.25±1.70, P3 80.50±1.29, respiratory frequency (times/minute) P0 21, 75±0.95, P121±0.81, P2 21.25±0.95, 21±0.81. The results of statistical analysis showed that the treatment had no significant effect (P>0.05) on body temperature, heart rate and respiratory frequency. Based on the research results obtained in this study, it can be concluded that giving sorghum silage and gamal leaves with concentrates at different balances gives the same results on the physiological status of local female goats.